2010
DOI: 10.1212/wnl.0b013e3181df09f7
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Neuro Images : Marked reduced apparent diffusion coefficient in acute multiple sclerosis lesion

Abstract: A 24-year-old woman presented with sudden right-sided weakness and aphasia. Brain MRI was performed 5 hours after symptoms onset. On diffusion-weighted imaging (DWI), the lesion showed a marked increase in signal intensity and an approximatively 70% mean apparent diffusion coefficient (ADC) decline as compared with the contralateral hemispheric white matter ( figure). The patient met diagnostic criteria for multiple sclerosis and other etiologies were excluded.ADC decline in acute multiple sclerosis lesions, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…MS is an inflammatory demyelinating disorder of the central nervous system (53–58). The initial symptoms can in some patients present as an acute pseudostroke with sudden onset of, eg, aphasia, deafness, or hemiplegia, thus mimicking an acute stroke (54–56). Most of these cases can be distinguished from ischemic stroke without difficulty by a careful evaluation of the patient's history, actual clinical findings, and findings on MRI.…”
Section: Maquerading Lesionsmentioning
confidence: 99%
“…MS is an inflammatory demyelinating disorder of the central nervous system (53–58). The initial symptoms can in some patients present as an acute pseudostroke with sudden onset of, eg, aphasia, deafness, or hemiplegia, thus mimicking an acute stroke (54–56). Most of these cases can be distinguished from ischemic stroke without difficulty by a careful evaluation of the patient's history, actual clinical findings, and findings on MRI.…”
Section: Maquerading Lesionsmentioning
confidence: 99%
“…7,11 Several recent case studies have reported a reduced ADC in acute demyelinating lesions and have emphasized their strokelike ADC appearance. [12][13][14][15] The temporal evolution of the ADC signal intensity has been well characterized in acute ischemic stroke showing typical phases of an initial reduction, followed by a pseudonormalization and an ADC elevation in the subacute-to-chronic phases. 9,16 In this study, we report the development of multiparametric MRI signal-intensity characteristics in hyperacute lesions of patients with MS with the main focus on the time course of the ADC signal intensity.…”
mentioning
confidence: 99%
“…[12][13][14][15]19 In contrast to MS, the evolution of the ADC has been analyzed in numerous studies in hyperacute ischemic stroke. 9,16 It may be for this reason that an ischemic mechanism has been suggested as involved in the ADC reduction.…”
mentioning
confidence: 99%
“…Second, the spinal cord has a relatively fixed position ensured by ligament connections, and it is thus particularly susceptible to micro-traumatic injury precipitating inflammation processes. Therefore, although small in diameter, spinal lesions can share the diffusion signal of MS larger/pseudotumoural/stroke-like lesions (DWI+/ADC−) due to the pronounced inflammatory process taking place [8,11,13,31,32]. Another factor that may contribute to the high prevalence of DWI+/ADC− pattern in our cohort could be related to the fact that the examination was conducted in the very early phase of the inflammatory process [11].…”
Section: Discussionmentioning
confidence: 99%